Nonlinear differential equations with asymptotically stable solutions - Slyusarchuk, V. E.; Слюсарчук, В. Е.; Слюсарчук, В. Е. (Institute of Mathematics, NAS of Ukraine, 1998)
We establish conditions of asymptotic stability of all solutions of the equation \(\frac{{dx}}{{dt}} = A(x)x\) , t≥0in a Banach space E in the case where σ(A(x)⊂{λ:Reλ